The effect of mergers and acquisitions on company’s performance - Shi, Yufei (2010)
This paper analyse the sample of 99 M&A transactions by U.S. publicly listed firm from 2003 to 2004 based on the Securities Data Corporation database. In the average, the acquiring firm has significant negative cumulative abnormal return from the M&A transaction base on the short-term analysis; the different type of the target firm and method of the payment, also play very important rule in the M&A, since the variation could arise from the different characteristics of the target and bid. Result indicate the smaller acquiring firm, and the smaller relative size between target and acquiring firm have smaller negative cumulative abnormal return to the acquiring firm than others; merger in the different industry have less negative return for acquiring firm compare to same industry acquisition; furthermore, the cash payment is more attractive compare to stock and other payment in three-day and five-day event windows, since they have smaller negative return for the acquiring firm, but not in the eleven-day event window.